Dual band antenna in licensed and unlicensed frequency bands based on superformula for 5G applications - Rasim Azeez Kadhim; Yaseen Naser Jurn; Mohammed Taih Gatte (Bulletin of Electrical Engineering and Informatics, 2023)
In this paper, the design and analysis of dual bands antenna is carried out. The ranges of frequencies are below 6 GHz and above 24 GHz. The superformula was used to design the proposed antenna where the curve profile of the proposed antenna is obtained by adjusting the six different parameters of the super-formula. The antenna shape likes the sunflower was mounted on flame retardant level 4 (FR4) substrate of dimensions of 32×32×1.5 mm3 and fed by a microstrip. The antenna is simulated using a computer simulation technology (CST) simulator. Results of the simulation showed that the antenna works in the licensed band (5.5–5.8 GHz) and the unlicensed band (24-40) GHz with voltage standing wave ratio (VSWR) less than 2 and return loss below -10 dBm. Also, the proposed design showed better performance than the normal ellipse-based antenna design with the same antenna dimensions.